2023
DOI: 10.1097/xcs.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Time to Whole Blood Transfusion in Hemorrhaging Civilian Trauma Patients: There Is Always Room for Improvement

Abstract: BACKGROUND: Whole blood (WB) is becoming the preferred product for the resuscitation of hemorrhaging trauma patients. However, there is a lack of data on the optimum timing of receiving WB. We aimed to assess the effect of time to WB transfusion on the outcomes of trauma patients. STUDY DESIGN: The American College of Surgeons TQIP 2017 to 2019 database was analyzed. Adult trauma patients who received at least 1 unit of WB within the first 2 hours of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…The study concluded that WB transfusion after 30 minutes was associated with an increased odds of death at 24 hours and in the hospital. Taken together, the present study and the study by Hosseinpour et al suggest that timing is an important variable in survival associated with WB. However, several critical differences exist between the present study and the study of Hosseinpour et al First, the study by Hosseinpour et al included any patient who received WB without any additional physiological criteria or consideration for the need for MTP.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The study concluded that WB transfusion after 30 minutes was associated with an increased odds of death at 24 hours and in the hospital. Taken together, the present study and the study by Hosseinpour et al suggest that timing is an important variable in survival associated with WB. However, several critical differences exist between the present study and the study of Hosseinpour et al First, the study by Hosseinpour et al included any patient who received WB without any additional physiological criteria or consideration for the need for MTP.…”
Section: Discussionsupporting
confidence: 83%
“…Taken together, the present study and the study by Hosseinpour et al suggest that timing is an important variable in survival associated with WB. However, several critical differences exist between the present study and the study of Hosseinpour et al First, the study by Hosseinpour et al included any patient who received WB without any additional physiological criteria or consideration for the need for MTP. Our study contributes to the narrative of these data, as it specifically evaluated patients with evidence of shock.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Given that exsanguinating hemorrhage is a primary source of preventable early death among trauma victims, 31 - 34 the CAB approach is logically beneficial, because it addresses the more lethal problem first. In fact, timely resuscitation, preferably with whole blood as the first product, has been shown to significantly improve the outcomes of trauma patients with exsanguinating injury.…”
Section: Role Of Euvolemic Resuscitation In Prioritizing Circulation ...mentioning
confidence: 99%